2008
DOI: 10.5194/acp-8-4085-2008
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and interpretation of gas phase formaldehyde concentrations obtained during the CHABLIS campaign in coastal Antarctica

Abstract: The measured seasonality is in line with previous observations from Neumayer station, with maximum in summer and minimum during the winter months, but with lower absolute concentrations throughout the year. The gas-phase production of HCHO was dominated by methane oxidation and a steadystate analysis showed that reactions of iodine and bromine species substantially reduced the predicted HCHO levels based upon in situ chemistry. This indicates a substantial additional HCHO source to be present that could be exp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 47 publications
1
46
0
Order By: Relevance
“…Kinetic measurements of the self reaction HO 2 + HO 2 have revealed the chaperone effect of water vapour enhancing the rate coefficient (Stone and Rowley, 2005). It has also been shown that the rate coefficient of the reaction HO 2 +NO 2 increase by 50 % from dry to humid atmospheric conditions (Sander and Peterson, 1984). In the Li et al (2014) study it was postulated that the reaction converts NO 2 to HONO with a yield of 100 % and this allowed a model to reproduce the observed levels of HONO, albeit under free-tropospheric conditions away from surfaces.…”
Section: Hono Box Model Approachmentioning
confidence: 99%
“…Kinetic measurements of the self reaction HO 2 + HO 2 have revealed the chaperone effect of water vapour enhancing the rate coefficient (Stone and Rowley, 2005). It has also been shown that the rate coefficient of the reaction HO 2 +NO 2 increase by 50 % from dry to humid atmospheric conditions (Sander and Peterson, 1984). In the Li et al (2014) study it was postulated that the reaction converts NO 2 to HONO with a yield of 100 % and this allowed a model to reproduce the observed levels of HONO, albeit under free-tropospheric conditions away from surfaces.…”
Section: Hono Box Model Approachmentioning
confidence: 99%
“…Formaldehyde measurements were made using an Aerolaser analyzer (Model AL 4021) that has a quantification limit of less than 50 pptv. The technique has been described in detail elsewhere [ Riedel et al , 1999; Salmon et al , 2008]. In brief, gaseous HCHO is scrubbed into a diluted sulfuric acid solution followed by reaction with the Hantzsch reagent, a dilute mixture of acetyl acetone, acetic acid, and ammonium acetate.…”
Section: Opale 2010–2011 Site Location and Instrumental Techniquesmentioning
confidence: 99%
“…These studies suggest that snowpack is a source of organic carbon to the atmosphere through possible outgassing and/or photochemical processes von Schneidemesser et al (2008) attributed the absence of a seasonal pattern in organic compounds in Greenland snow (hopanes, PAHs, alkanes, alkanoic acids) to possible post-depositional processing occurring in the snowpack. Other studies also point to the fact that concentrations of gas phase formaldehyde (HCHO) measured in the Arctic (Mabilia et al, 2007) and in Antarctica (Salmon et al, 2008) cannot be explained by known gas-phase chemistry without considering an additional source of HCHO from the snowpack, in support of previous observations Sumner and Shepson, 1999). In further support of these observations, Barret et al (2011a) showed that the seasonal snowpack near Barrow, Alaska, was a source of HCHO and that, while most of the HCHO produced was released to the atmosphere, a small fraction was incorporated into surface snow crystals by solid state diffusion.…”
Section: Atmosmentioning
confidence: 99%